Pain Management and Opioid Regulation: Continuing Public Health Challenges - Bonnie, Richard J. (Am J Public Health, 2019)
The still-growing US opioid epidemic lies at the intersection of two major public health challenges: reducing suffering from pain and containing the rising toll of harms associated with the use of opioids medications. Responding successfully to these challenges requires a substantial investment in surveillance and research on many fronts and a coordinated policy response by federal and state agencies and stakeholder organizations. A 2017 report of the National Academies of Sciences, Engineering and Medicine (NASEM) called for improved methods of measuring pain and the effects of alternative modalities of treatment as well as intensive surveillance of opioid-related harms; urged a long-term cultural transformation of how pain is perceived, assessed and treated; and outlined a comprehensive and balanced public health framework to guide Food and Drug Administration approval, monitoring, and review of opioids. We, authors of the NASEM report, use the articles published in this special section of AJPH as a platform for commenting on the public health burden of pain, the role of opioids in managing pain, global disparities in access to opioids for pain management, divergent approaches to opioid regulation, and the challenge of striking a reasonable balance between the needs of patients in pain and the prevention of opioid-related harms.